Microparticle manipulation by standing surface acoustic waves with dual-frequency excitations - Zhou, Yufeng (2020)
We demonstrate a method for increasing the tuning ability of a standing surface acoustic wave (SSAW) for microparticles manipulation in a lab-on-a-chip (LOC) system. The simultaneous excitation of the fundamental frequency and its third harmonic, which is termed as dual-frequency excitation, to a pair of interdigital transducers (IDTs) could generate a new type of standing acoustic waves in a microfluidic channel. Varying the power and the phase in the dual-frequency excitation signals results in a reconfigurable field of the acoustic radiation force applied to the microparticles across the microchannel (e.g., the number and location of the pressure nodes and the microparticle concentrations at the corresponding pressure nodes). This article demonstrates that the motion time of the microparticle to only one pressure node can be reduced ~2-fold at the power ratio of the fundamental frequency greater than ~90%. In contrast, there are three pressure nodes in the microchannel if less than this threshold. Furthermore, adjusting the initial phase between the fundamental frequency and the third harmonic results in different motion rates of the three SSAW pressure nodes, as well as in the percentage of microparticles at each pressure node in the microchannel. There is a good agreement between the experimental observation and the numerical predictions. This novel excitation method can easily and non-invasively integrate into the LOC system, with a wide tenability and only a few changes to the experimental set-up.